Writing of the literary essay on the basis of new technology of K. Bitibayeva (According to the epic novel by M. Auezov «the Way of Abay») (Eurasian Journal of Philology Science and Education, 2019)
This articlet is about a technique of writing of the essay on the basis of the new technology ofoutstanding person of the Kazakh pedagogics K.O. Bitibayeva. The technique of writing of the essayin detail is analyzed and considered on the agenda of the modern school program. K. Bitibayeva’s technology «Oi tastay, oilanu» represents a model of pedagogical experience of the author which purposeis awakening of informative and creative abilities and research competences of pupils. It is confirmed,proceeding from own experience, on the example of texts of the epic of M. Auezov «the Way of Abay»,the developing interest, motivation and cogitative activity of pupils.